The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/md21010017
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Glucose-6-Phosphate Dehydrogenase Overexpression Strain of Schizochytrium sp. H016 to Improve Docosahexaenoic Acid Production

Abstract: Docosahexaenoic acid (DHA) is an important omega-3 polyunsaturated fatty acid (PUFA) that plays a critical physiological role in human health. Schizochytrium sp. is considered an excellent strain for DHA production, but the synthesis of DHA is limited by the availability of nicotinamide adenine dinucleotide phosphate (NADPH). In this study, the endogenous glucose-6-phosphate dehydrogenase (G6PD) gene was overexpressed in Schizochytrium sp. H016. Results demonstrated that G6PD overexpression increased the avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Similarly, overexpression of G6PDH in Schizochytrium sp. H016 promoted strain growth and glucose consumption and thus increased the availability of NADPH as well as docosahexaenoic acid production (Sundara Sekar et al, 2017 ; Feng et al, 2022 ). Therefore, increasing the G6PDH expression level in H. marmoreus could efficiently improve the glucose assimilation rate and promote mycelial growth and biomass production, which might contribute to increasing carbon flux into the PPP of H. marmoreus .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, overexpression of G6PDH in Schizochytrium sp. H016 promoted strain growth and glucose consumption and thus increased the availability of NADPH as well as docosahexaenoic acid production (Sundara Sekar et al, 2017 ; Feng et al, 2022 ). Therefore, increasing the G6PDH expression level in H. marmoreus could efficiently improve the glucose assimilation rate and promote mycelial growth and biomass production, which might contribute to increasing carbon flux into the PPP of H. marmoreus .…”
Section: Resultsmentioning
confidence: 99%
“…Schizochytrium is considered an excellent strain for DHA production, but the DHA production is limited by the availability of NADPH. Feng et al found that overexpression of G6PD in Schizochytrium increased the availability of NADPH, which ultimately led to an increase in lipid accumulation and DHA production [51]. The lipid productivity of photosynthetic microalgae is lower than heterotrophic oil-producing microorganisms, due to slower growth caused by photosynthetic autotrophy.…”
Section: Bypass Pathwaysmentioning
confidence: 99%